Cost structure and comparative advantage of export supply chain of Chu-mango in the Mekong Delta, Vietnam - Vo Tuan Truong, Kiet Hong; Sidique, Shaufique Fahmi; Shamsudin, Mad Nasir; Abdul Hadi, Ahmad Hanis Izani (CENTMA Research, 2022)
This study aims at identifying the production cost structure of the main actors in the Chu-mango supply chain at the market price, and the comparative advantage of the export supply chain at the social price. The comparative advantage of the Chu-mango trade system is measured by the domestic resource cost per shadow exchange rate (DRC/SER ratio) based on a systematic supply chain management approach. It is based on 603 observations among main actors in the Mekong Delta, Vietnam. The results indicate that the export supply chain of Chu-mango in the Mekong Delta has three main channels. The total production cost of export channel 1 triples that of export channels 2 and 3. The main reason for this disparity is Chu-mango grade 1 and high test and transport costs (airplane), whereas channel 2 is mango grades 3 and 4 (shipping line), and channel 3 is mango grade 2 (roadway). The result was three export channels of the Chu-mango trade system to obtain EE with a DRC/SER ratio of less than one. In export channel 1, the DRC/SER ratios are 0.52, 0.53, and 0.49 for seasons 1, 2, and 3, respectively. In export channel 2, these numbers were 0.66, 0.67, and 0.62 for seasons 1, 2, and 3, respectively. In export channel 3, the DRC/SER ratios are 0.49, 0.53, and 0.42 for seasons 1, 2, and 3, respectively. Policymakers and governments need export business incentives based on better exploitation of the comparative advantage to contribute to the sustainable development and economic growth of Chu-mango. The findings of this study contribute to the literature on comparative advantage analysis of export supply chains for other tropical fruits and vegetables, and confirm that the right value of the Ricardian model in international trade is valid and applicable to the real world.